1987
DOI: 10.1002/ijc.2910390510
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence of collagenolytic activity in ductal infiltrating carcinoma of the human breast

Abstract: The stroma of ductal infiltrating carcinoma of the human breast shows characteristic and localized areas of collagen rarefaction and fragmentation. This finding has been correlated with a peculiar type of fibrillar damage, observed in a small percentage of collagen fibrils isolated in the native state from the tumour stroma. The same pattern of lesion has been reproduced in vitro by human collagenase digestion on reconstituted fibrils. No effect has been detected by other nonspecific proteases in the same syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These pathways, subjected to a dynamic and zonal turn‐over of synthetic and degradative events (e.g. [37]), conceivably participate in feeding or restraining the autocrine/paracrine circuits which are likely to exist between PTHrP and sensitive breast cancer (and other) cells; the resulting differential effects on cell behavior might contribute in concert with other microenvironmental signals to control tumor growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways, subjected to a dynamic and zonal turn‐over of synthetic and degradative events (e.g. [37]), conceivably participate in feeding or restraining the autocrine/paracrine circuits which are likely to exist between PTHrP and sensitive breast cancer (and other) cells; the resulting differential effects on cell behavior might contribute in concert with other microenvironmental signals to control tumor growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The degradation of the collagen fibrils in breast tissue is known to occur with infiltrating disease. [9][10][11][12] Tumor cell secreted proteases cause degradation of basement membranes around epithelial cells as well as the extracellular matrix ͑ECM͒, which are abundant in connective proteins, such as collagen. 13,14 The interactions of tumor cells with these connective tissues are important events in the metastasis of cancer, and the implication that cancer cells become invasive by adhesion to, and degradation of, the basement membranes and ECM is central to the activity of tumor cells entering and exiting blood vessels and lymphatics in order to proliferate at distant sites.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 Degradation of fibrillar collagen in cancerous tissues, which has been seen with electron micrograph images, may indicate that the new collagen is unable to aggregate properly to reconstitute the typical bundles found in healthy tissues. 11,12 It has also been suggested that the accumulation of altered collagen molecules during cancer progression impairs the correct supramolecular organization of the collagenous stroma and may provide a permissive pathway for the invasive growth of neoplastic cells. 5,16 Since SAXS is sensitive to the supramolecular structures of tissues, it can be used to evaluate if systematic variations in structure are correlated with disease progression, and hence to improved understanding of the spread of invasive disease.…”
Section: Introductionmentioning
confidence: 99%
“…The invasive properties of primary tumours are partially dependent on degradation of the extracellular matrix (ECM), which under normal circumstances is crucial for cell-cell and cell-substratum interaction (7). Increased collagen degradation and reduced collagen synthesis are key features in the series of pathological events that aid tumour cell invasion and metastasis (8,9).…”
Section: Introductionmentioning
confidence: 99%